Facile preparation of conductive carbon-based membranes on dielectric substrates - Liu, Guoran; Xu, Guanchen (Frontiers in Chemistry, 2023)
Graphene has been attracted much attention due to its outstanding chemical and physical properties. The excellent electronic conductivity is considered to be the most possible one for applications. To address this anticipation, we developed a new method for synthesizing conductive carbon membrane on dielectric substrates at a low temperature though a thermodynamic driven process. Though the obtained film has a low-crystallinity structure, the electrical, wetting and optical properties are acceptable in practice. Moreover, the precursors are pervasive over the substrates. This new method opens up a new avenue for the growth of carbon membrane and may facilitate the applications of transparent electrodes, potential plasma-free surface-enhanced Raman scattering (SERS) substrate for reality.